Facile fabrication of flower-like binary metal oxide as a potential electrode material for high-performance hybrid supercapacitors. Issue 7 (1st April 2022) - Sivakumar, Periyasamy; Raj, C. Justin; Park, JeongWon; Jung, Hyun
Abstract: Developing efficient electrode material with rational design and structure remains a crucial and great challenge for the significant improvement of high-performance hybrid supercapacitors (HSCs). Particularly, the performance of the HSCs can be largely enhanced by designing the battery-type Faradaic material with well-defined morphology and defective engineering. Here, a facile and effective strategy is utilized to develop oxygen-deficient flower-like three-dimensional NiMoO4−δ (Od -NMO) nanomaterial via hydrothermal process and following thermal-treatment under an inert-gas atmosphere. The presence of oxygen deficiency in the Od -NMO is evaluated utilizing various spectroscopy techniques by comparing the pristine NiMoO4 (P-NMO) heat treated under an ambient atmosphere. The electrochemical studies indicate that the oxygen defect sites in the Od -NMO electrode have a considerable role in the betterment of supercapacitive performances. Hence, the Od -NMO electrode provides a large specific capacity of 789 mA h g −1 at 1 A g −1 with an excellent rate capability than the P-NMO (579 mA h g −1 ). Besides, the fabricated HSC based on Od -NMO flower and activated carbon as the positive and negative electrodes, delivers a specific capacitance as high as 153 F g −1 and accomplishes a large energy density (47.76 W h kg −1 ) and power density (51.69 kW kg −1 ) with improved long-term stability.